Storyworlds: the straw house - Riordan, James; Dunton, Trevor (Heinemann UK, 1996)
"Part of the "Storyworlds" series, this is a pack of the four Stage Five traditional tales. Each story reinforces between 20 and 40 new words, and adopts a broadening approach, to encourage the move to independent reading. Continued repetition of text should help to build the child's confidence."